The Practice of Statistics in the Life Sciences - Baldi, Brigitte Moore, David S. (W.H. Freeman and Company, 2012)
This text provides an introduction to the uses and applications of statistics in the life sciences with a data analysis approach. In this edition a quarter of the examples and exercises have been updated and new Large Data Set exercises have been added. (This title is market restricted. Please consult your sales representative for availability.)